2022
DOI: 10.3390/metabo12090844
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Comparative Analysis of Cordyceps pseudotenuipes with Other Species from Cordyceps

Abstract: The whole genome of Cordyceps pseudotenuipes was sequenced, annotated, and compared with three related species to characterize the genome. The antibiotics and Secondary Metabolites Analysis Shell (antiSMASH) and local BLAST analysis were used to explore the secondary metabolites (SMs) and biosynthesis gene clusters (BGCs) of the genus Cordyceps. The genome-wide basic characteristics of C. pseudotenuipes, C. tenuipes, C. cicadae, and C. militaris revealed unequal genome size, with C. cicadae as the largest (34.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The results of the 14 genome-wide data analysis for 13 species of Cordycipitaceae indicated that C. cicadae region 87.1, region 56.2, region 27.1 and region 117.1 might exist to catalyze the synthesis of the BEA, dimethylcoprogen, wortmanamide A/B and viriditoxin, respectively, in agreement with our previous analysis of C. cicadae [28]. Among the 14 genomes, the potential gene clusters of acetylaranotin, bassianolide, dimethylcoprogen, epichloenin A, aspyridone A, curvupallide-B, fumosorinone, phomasetin, wortmanamide A/B, 4-epi-15-epi-brefeldin A, alternapyrone, asperfuranone, bikaverin, citrinin, fujikurin, solanapyrone D and viriditoxin were also excavated.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the 14 genome-wide data analysis for 13 species of Cordycipitaceae indicated that C. cicadae region 87.1, region 56.2, region 27.1 and region 117.1 might exist to catalyze the synthesis of the BEA, dimethylcoprogen, wortmanamide A/B and viriditoxin, respectively, in agreement with our previous analysis of C. cicadae [28]. Among the 14 genomes, the potential gene clusters of acetylaranotin, bassianolide, dimethylcoprogen, epichloenin A, aspyridone A, curvupallide-B, fumosorinone, phomasetin, wortmanamide A/B, 4-epi-15-epi-brefeldin A, alternapyrone, asperfuranone, bikaverin, citrinin, fujikurin, solanapyrone D and viriditoxin were also excavated.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, we conducted comparative genomic studies on the SM BGCs of Cordyceps and found that even related species of the same genus had different genome sizes, GC contents and assumed quantities of PKS, NRPS, hybrid PKS-NRPS, hybrid PKS-Other and terpene. Seven compounds, namely dimethylcoprogen, epichloenin A, wortmanamide A/B, phomasetin, fumosorinone, beauvericin, and viriditoxin, have been discovered as putative BGCs [28]. In this study, whole genomes of S. hepiali and S. yunnanensis YFCC 1527 were sequenced and annotated, and the basic characteristics and gene mining were compared with 14 genomes of 13 species belonging to 7 genera in the family of Cordycipitaceae (i.e., Akanthomyces, Cordyceps, Beauveria, Lecanicillium, Gamszarea, Samsoniella, and Simplicillium).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained that the sister species of Cordyceps, C. pseudotenuipes H. Yu, Q. Y. Dong, and Y. Wang and C. tenuipes (Peck) Kepler, B. Shrestha, and Spatafora, had the potential to synthesize dimethylcoprogen, epichloenin A, wortmanamide A/B, beauvericin, etc. (Lu et al, 2022). The number of NPRS-like, PR-PKS, Hybrid PKS-NRPS-Other and Hybrid By comparing the transcriptomes, Will et al (2020) pointed out that fusarin C might act as a virulence factor to alter ant behavior.…”
Section: Discussionmentioning
confidence: 99%